An application of the standardised reference extract quantification strategy in the quality control of ginseng infusions by liquid chromatography with mass spectrometric detection. Issue 6 (11th May 2022) - Semenova, Irina; Bryskina, Diana; Cvetanović Kljakić, Aleksandra; Ražić, Slavica; Ananiev, Vasiliy; Rodin, Igor; Shpigun, Oleg; Stavrianidi, Andrey
Abstract: Introduction: Limited availability of individual standards is a bottleneck for quality control of functional foods and natural medicines. The use of standard mixtures or secondary standards is a possible alternative in this case. Earlier, an approach known as standardised reference extract (RE) strategy was introduced for HPLC‐UV analysis of different plant materials; however, its application in HPLC‐MS analysis has not been investigated. Objective: To establish an HPLC‐MS‐based RE method for determination of ginsenoside content in ginseng infusions using commercially available extract reference material of Panax quinquefolius L. Results: The developed HPLC‐MS method was validated as precise (1.1%–9.4% intra‐day variation; 1.6%–12.8% inter‐day variation) and highly sensitive [limit of detection (LOD): 1–40 ng/mL; limit of quantification (LOQ): 4–120 ng/mL]. The stability of samples was satisfactory (5.7%–16.3%). The RE quantification method was compared with the external standard method, and the obtained difference was not significant, mostly in the range of 5%–10%. Matrix effects for the diluted samples of RE and ginseng infusions, determined via the standard addition method, were in the range of 85%–115% and 80%–126%, respectively, and were also positively correlated with the ginsenoside concentration. Eleven batches of ginseng infusions from different manufacturers were analysed using the established method. Conclusion: The method for HPLC‐MS‐based ginsenoside quantification using RE as a secondary standard was established for the first time. The results of this study demonstrate that the application of the standardised RE strategy in HPLC‐MS can minimise the matrix effect‐related error in addition to the cost‐effective quality control of herbal products, foods, and traditional medicines. Abstract : Limited availability of individual standards is a bottleneck for quality control of functional foods and other products made of plant materials, and the use of secondary standards is a viable solution for this problem. For rapid, inexpensive, and comprehensive quality control of ginseng products containing dozens of major and minor saponins, HPLC‐MS and standardized reference extract strategy were employed. The developed method was validated, and matrix effects for diluted reference extract and ginseng infusion samples were determined via standard‐addition method.